Adhesion and running speed of a tropical arboreal ant (Cephalotes atratus) on wet substrates. Issue 11 (14th November 2018) - Stark, Alyssa Y.; Yanoviak, Stephen P.
Abstract : In the tropical forest canopy, wingless worker ants must cling to and run along diverse vegetative surfaces with little protection from sun, wind and rain. Ants rely in part on their tiny adhesive tarsal pads to maintain sufficient contact with substrates to prevent falls under these varied conditions. Here, we examined the effects of substrate wettability and surface water on the tarsal pad adhesive performance of a common tropical arboreal ant. Ant adhesion was consistently higher on an intermediately wetting substrate (static water contact angle ca 90°) when resisting both perpendicular (normal) force and parallel (shear) force. Normal adhesion was maintained on intermediately wetting and hydrophobic substrates following the addition of rain-mimicking water droplets, whereas shear adhesion declined on all substrate types tested after wetting. Ant running speed was slower on wet substrates. On wood substrates, normal and shear adhesion declined with increasing wetness from dry, to misted, to water-soaked. These differences probably contributed to lower ant running speed on wet wood. The results of this study provide the first quantitative assessment of tropical arboreal ant adhesive performance under substrate conditions that are commonly encountered in the rainforest canopy.